Activation of MYC, a bona fide client of HSP90, contributes to intrinsic ibrutinib resistance in mantle cell lymphoma - Jimmy Lee; Liang Leo Zhang; Wenjun Wu; Hui Guo; Yan Li; Madina Sukhanova; Girish Venkataraman; Hui Zhang; Mir Alikhan; Pin Lu; Ailin Guo; Natalie Galanina; et al. (Blood Advances, 2018)
Abstract: The BTK inhibitor ibrutinib has demonstrated a remarkable therapeutic effect in mantle cell lymphoma (MCL). However, approximately one-third of patients do not respond to the drug initially. To identify the mechanisms underlying primary ibrutinib resistance in MCL, we analyzed the transcriptome changes in ibrutinib-sensitive and ibrutinib-resistant cell lines on ibrutinib treatment. We found that MYC gene signature was suppressed by ibrutinib in sensitive but not resistant cell lines. We demonstrated that MYC gene was structurally abnormal and MYC protein was overexpressed in MCL cells. Further, MYC knockdown with RNA interference inhibited cell growth in ibrutinib-sensitive as well as ibrutinib-resistant cells. We explored the possibility of inhibiting MYC through HSP90 inhibition. The chaperon protein is overexpressed in both cell lines and primary MCL cells from the patients. We demonstrated that MYC is a bona fide client of HSP90 in the context of MCL by both immunoprecipitation and chemical precipitation. Furthermore, inhibition of HSP90 using PU-H71 induced apoptosis and caused cell cycle arrest. PU-H71 also demonstrates strong and relatively specific inhibition of the MYC transcriptional program compared with other oncogenic pathways. In a MCL patient-derived xenograft model, the HSP90 inhibitor retards tumor growth and prolongs survival. Last, we showed that PU-H71 induced apoptosis and downregulated MYC protein in MCL cells derived from patients who were clinically resistant to ibrutinib. In conclusion, MYC activity underlies intrinsic resistance to ibrutinib in MCL. As a client protein of HSP90, MYC can be inhibited via PU-H71 to overcome primary ibrutinib resistance.